Educational Methods for Providing Additional Food to Toddlers with Malnutrition - Duka, Melanya Jelita; Sambriong, Maria; Kapitan, Meiyeriance (Sean Institute, 2025)
Malnutrition or undernutrition is a condition where a person has below average nutrition. Undernutrition is caused by a person lacking intake of carbohydrates, protein, fat and vitamins that are very much needed by the body. The purpose of the study was to obtain an overview of the educational method for providing additional food to parents with undernourished toddlers at the Alak Health Center. This type of research is a study using a descriptive design using a case study approach method to explore the educational method for providing additional food to children with undernourishment at the Alak Health Center. The subjects of the case study were 3 toddler patients who experienced undernourishment at the Alak Health Center. The results of this study showed an increase in respondents' knowledge about providing additional food to toddlers with undernourishment. This proves that education on providing additional food with the counseling method and flipchart media can increase knowledge about providing additional food to toddlers with undernourishment. Providing education with the counseling method using flipchart media can increase mothers' knowledge about providing additional food to toddlers with undernourishment.